River Response to Deforestation, 1832-1971, Platte River, Grant County Wisconsin - Corcoran, William T. (My University, 1972)
Man's impact on his environment is currently a popular subject of discourse; it is a topic of genuine importance in a world of increasing population and increasing utilization of natural resources. This thesis is concerned with man's ability to modify the hydrologic environment of drainage basins. Specific focus is given to man-induced adjustments in hydraulic variables that are regulated by a balance between surface runoff and sediment yield. Land use changes associated with European settlement have greatly altered rates of runoff and sediment yield and have subsequently produced considerable changes in cross-sectional and planimetric morphologies of Southwestern Wisconsin streams and rivers.
Graphs; Figures; Tables; Map; Plates; Bibliography
Keywords: Drainage Basins; Grant County; Deforestation; Platte River